Case Report: Various Clinical Manifestations Caused by Varicella-Zoster Virus in a Family - Qinghong Meng; Bingsong Wang; Xianlai Zhang; Zhen Li; Wenjie Wang; Kaihu Yao (Frontiers Media S.A., 2022)
A family cluster of varicella-zoster virus (VZV) infections was reported. Four family members (two children and their parents) continuously develop varicella after the grandmother's herpes zoster. The unvaccinated 16-month-old infant and his mother developed primary varicella with atypical clinical presentation; however, his 28-year-old father presented with a typical generalized vesicular rash. His vaccinated 4-year-old sister was clinically mild, which could be defined as a breakthrough varicella case. They infected the same virus strain but presented various clinical forms.